Education M-Health Android-based Smartphone Media Application "Mama ASIX" for Third Trimester Pregnant Women as Preparation for Exclusive Breastfeeding - Mariza Mustika Dewi; Masrifan Djamil; M. Choiroel Anwar (Journal of Health Promotion and Behavior, 2019)
Background: The lack of exclusive breastfeeding coverage is partly due to the low knowledge of mothers and families regarding the benefits and the right way to breastfeed and not maximally activities education, socialization, advocacy, and campaigns related to exclusive breastfeeding. The purpose of this study was to prove the effectiveness of education M-Health using the media application of smartphone Android-based “Mama ASIX" in third-trimester pregnant women as preparations for exclusive breastfeeding mothers.Subjects and Method: This was a quasi-experiment study with non-equivalent pretest-posttest with control group design. This study was conducted at the Genuk and Pegandan health centers in Semarang, Central Java. The subjects of 36 pregnant women in the third trimester were selected by probability sampling technique were the type of purposive sampling. The independent variables were the application of "Mama ASIX" application and counseling with leaflet, while the dependent variable was the knowledge and attitude of breastfeeding. The instrument in the study is a questionnaire. Data were analyzed using the Wilcoxon test and the Mann-Whitney test.Results: Knowledge about breastfeeding increased (mean = 67.78 to 91.33, 95%CI, p< 0.001), breastfeeding attitudes by mothers increased (mean= 68.67 to 85.94 95%CI, p= 0.001), the application "Mama ASIX" is more effective in increasing knowledge of breastfeeding (difference in mean= 23.55, 95%CI, p= 0.030) and the attitude of breastfeeding (difference in mean = 17.27, 95%CI, p= 0.029).Conclusion: Education M-Health using the Android-based smartphone media application "Mama ASIX" in the third trimester pregnant women can help mothers prepare exclusive breastfeeding by increasing the knowledge and attitude of breastfeeding for their babies.Keywords: Knowledge, Attitude, Education, MHealth, AndroidCorrespondence: Mariza Mustika Dewi. Applied Midwifery, Graduate Program, School of Health Polytechnics, Ministry of Health Semarang. Jl.Tirto Agung, Pedalangan, Banyumanik, Semarang, Central Java. Email: dewimariza1803@gmail.com. Mobile: +6585865776356.Journal of Health Promotion and Behavior (2019), 4(2): 98-109https://doi.org/10.26911/thejhpb.2019.04.02.02